The others of Islamist civilizational populism in AKP’s Turkey - Yilmaz, Ihsan; Mohamad Shukri, Syaza Farhana; Shakil, Kainat (2023)
Turkey’s history and politics allow populism and Sunni Islamist civilizationalism to thrive. The ruling Justice and Development Party’s (AKP) use of Islamist authoritarian populism in its second decade of power has widened its “otherization” of political opponents, non-Muslims, non-Sunnis, ethnic minorities, vulnerable groups, and all those who reject the AKP’s views and democratic transgressions. To comprehend how Erdogan and his deft colleagues leverage identities of Sunni Islam and Turkish ethnicity, alongside pre-existing collective fears to develop populist authoritarianism, in this article, each category of “the others” is investigated through the lens of civilizational populism. This article specifically delves into the “otherization” process towards the Kemalists, secularists and leftists/liberals, Kurds, Alevis, and practicing Sunni Muslim Gulen Movement. The different methods of AKP’s civilizational populist “otherization” continues to polarize an already divided Turkish nation, generating incalculable harm.